Strategi Pensiunan Perkebunan PT Socfin Indonesia Socfindo Dalam Kelangsungan Hidup Pasca Pensiun di Desa Dengon Sari - Atika Nadila; Andri Soemitra; Anggita Utami; Amin Rahmad Panjaitan; Istiqomah Ayu Syahputri (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Retirement is an old age guarantee and in return for employees who have devoted years to PT. Socfindo. In the end it became the duty of each individual to try to guarantee his parents' day, and for this each PT. Socfindo employee is obliged to enter into the participant of a social insurance agency formed by PT. Socfindo. As pension is not only a guarantee of the old days but also a recompension of the benefits, PT. Socfindo gives his employees severance. The frequent effect of retirement is that one's unpreparedness faces retirement. Such conditions are also usually followed by changes, physical setbacks, and setbacks. Retirement is the end of a person's life pattern in his working life, or it can be referred to asa transition to a new life pattern. Key Words: Retired, Welfare In Life, PT. Socfindo Employee.